PENGEMBANGAN MODUL AJAR BERORIENTASI MODEL PROBLEM BASED LEARNING BERBANTUAN METODE 3R UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Hamidah, Nurul; Ira Rengganis; Lea Christina Br Ginting (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low level of critical thinking skills and the lack of student awareness regarding waste issues in their surrounding environment. One of the contributing factors is the use of learning materials that are not aligned with students' needs. Therefore, the purpose of this study is to develop a teaching module oriented toward the Problem-Based Learning model, supported by the 3R (Reduce, Reuse, Recycle) method, to improve the critical thinking skills of students in Phase B. This study adopts the Design and Development (D&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques include observation, interviews, questionnaires, and tests, with both qualitative and quantitative data analysis. The initial design of the module includes components such as the front cover, preface, table of contents, general information, core competencies, learning activities, conclusion, appendices, and back cover. Expert validation was conducted twice: before and after revision. The feasibility scores increased after revision, with assessments from subject matter experts improving from 94.2% to 99.4%, media experts from 91.4% to 94.8%, and learning experts from 86.4% to 90.6%. The overall average increased from 90.6% to 94.9%. Implementation of the module with fourth-grade Phase B students showed improved learning outcomes. The average pretest score increased from 49.7 to 80.9 in the posttest. The N-Gain score of 0.61 indicates a “Moderate” improvement. Therefore, this PBL-oriented module using the 3R method is effective in improving students’ critical thinking skills.